Peningkatan Hasil Belajar Passing Bawah Bola Voli Menggunakan Balon pada Kelas VIII SMP N 3 Limbur Lubuk Mengkuang - Sonia Ananta (CV. Master Literasi Indonesia, 2025)
This research stems from the use of conventional teaching methods, which have been proven less effective in improving students' underhand passing (bump) skills in volleyball. When this method is applied, students appear unenthusiastic and easily frustrated when they fail to perform the underhand pass correctly. The low learning outcomes are also influenced by the lack of appropriate learning media that align with the characteristics of elementary school students, leading to reduced interest in practicing volleyball passing skills. This study is a classroom action research (CAR) that observes the teaching and learning processes at school. The subjects of this research were 31 fifth-grade students of SMP N 3 Limbur Lubuk Mengkuang. The study was conducted in two cycles, each consisting of planning, action implementation with observation, and reflection. This classroom action research was carried out in the odd semester of the 2024/2025 academic year at SMP N 3 Limbur Lubuk Mengkuang, class VIII. Data was collected through observation sheets and documentation. The results of data analysis showed that the use of balloons can improve both the learning process and the outcomes in underhand volleyball passing. This is evident from the teacher’s teaching process, which showed an average of 73% in Cycle I and improved to 84% in Cycle II. Similarly, student learning outcomes increased from 45% in Cycle I to 72.5% in Cycle II. Based on these results, using balloons as a learning medium for teaching underhand passing in volleyball is recommended for further implementation and development.